Assessment of efficacy of promethazine on seizure activity and its interactions with antiepileptic drugs lorazepam and sodium valproate in rats - Shinde, Vinod; Warudkar, Sandesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Presently available antiepileptic drugs are effective in controlling seizures in more than half of patients of all epilepsy but use is often limited by adverse effects. H1 receptor antagonists, have a controversial status in patients of epilepsy. Both pro and antiepileptic effect has been documented in various animal studies. Hence, this study was designed to see the effect of promethazine, an H1 antihistaminic drug and its interactions with antiepileptic drugs lorazepam and sodium valproate in rats. Methods: The effect of promethazine (10 mg/kg) and its interactions with antiepileptic drugs lorazepam and sodium valproate was assessed by using maximal electroshock seizures (MES) and chemoshock pentylenetetrazol (PTZ) method. Results: Promethazine along with lorazepam and sodium valproate in subtherapeutic doses exerted significant protection against MES induced seizures whereas no such protection was observed with PTZ method rather the seizure threshold was reduced. Conclusions: Subtherapeutic doses of promethazine alone and in combination with lorazepam and sodium valproate showed protection against seizures in MES method. However, proconvulsant effect was seen with PTZ method. This shows dual behavior of promethazine on MES and PTZ induced seizures.